2003
DOI: 10.1063/1.1579680
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the electronic structure of a newly synthesized two-photon polymerization initiator

Abstract: Time-dependent hybrid density functional theory in combination with polarized continuum model has been applied to study the solvent effects on the geometrical and electronic structures, as well as one- and two-photon absorption processes, of a newly synthesized asymmetrical charge-transfer (CT) two-photon absorption (TPA) organic molecule. The TPA cross section calculated from a generalized two-state model and solvatochromic shift of the CT state are found to be solvent dependent, for which a nonmonotonic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 15 publications
4
52
0
Order By: Relevance
“…34,35,49,50 However, it is unclear why 1L exhibits enhanced 2PA properties in toluene and its 2PA efficiency decreases monotonically as the solvent polarity increases. Maybe this is due to specic solvent-solute interactions in polar solvents redistributing the energetics of the excited state and changing the excitation transition dipole moments.…”
Section: 48mentioning
confidence: 99%
“…34,35,49,50 However, it is unclear why 1L exhibits enhanced 2PA properties in toluene and its 2PA efficiency decreases monotonically as the solvent polarity increases. Maybe this is due to specic solvent-solute interactions in polar solvents redistributing the energetics of the excited state and changing the excitation transition dipole moments.…”
Section: 48mentioning
confidence: 99%
“…Our experimental results show that the four new compounds have large enough TPA cross-sections which can induce polymerization of acrylate. The photopolymerization mechanism of the four initiators is still unknown, according to Wang et al [23] .…”
Section: Two-photon Polymerizationmentioning
confidence: 99%
“…In the presence of the monomer bulk, polar acrylate, the energy barrier can be drastically reduced by the short-range molecular interaction. As a result, the electron hopping to the monomer way rapidly initiated [11]. The interaction of antibonding with bonding orbitals result in a loss of energy, which is proportional to the contribution of intra-exciplex [14].…”
Section: Mechanism Of Two-photon-induced Polymerizationmentioning
confidence: 99%
“…It was suggested that the polymerization rate is associated with the pumping rate of the CT state of the initiator [10,11]. As for molecules having the general structural motif D--D are sufficiently electron rich, it was noted that they could activate the polymerized reaction by an electron transfer, subsequent to two-photon excitation [3,9,12,13,22].…”
Section: Mechanism Of Two-photon-induced Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation